2005
DOI: 10.4040/jkan.2005.35.7.1295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abdominal Breathing Training Using Biofeedback on Stress, Immune Response and Quality of Life in Patients with a Mastectomy for Breast Cancer

Abstract: Abdominal breathing training using biofeedback improves quality of life in breast cancer patients after a mastectomy. However, the mechanism of this beneficial effect and stress response requires further investigation with special consideration in subject selection and frequency of measurement. Nurses should consider this strategy as a standard nursing intervention for people living with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 1 publication
1
3
0
3
Order By: Relevance
“…With regard to the mood states, we found a significant reduction of tension, anger, and depressive feelings after both breathing interventions, indicating a more general reduction of the stress level. As has been shown, several studies parallel to our findings have demonstrated a reduction of negative feelings due to breathing exercises both in patients with chronic pain and healthy controls [2-4, 18,35,[88][89][90][91][92]. In contrast to our findings that only rDSB is able to selectively modify autonomic response and pain perception, mood processing was affected in a similar manner irrespective of the breathing maneuver.…”
Section: Adsbsupporting
confidence: 78%
“…With regard to the mood states, we found a significant reduction of tension, anger, and depressive feelings after both breathing interventions, indicating a more general reduction of the stress level. As has been shown, several studies parallel to our findings have demonstrated a reduction of negative feelings due to breathing exercises both in patients with chronic pain and healthy controls [2-4, 18,35,[88][89][90][91][92]. In contrast to our findings that only rDSB is able to selectively modify autonomic response and pain perception, mood processing was affected in a similar manner irrespective of the breathing maneuver.…”
Section: Adsbsupporting
confidence: 78%
“…Most studies on quality of life have been focused on chronical diseases or others that somehow have a high impact on the patient's lifestyle, and sometimes requires the patient to make changes to life habits. In cancer in particular, QOL has been studies for more than three decades, with research works focused on particular cancer types and the impact on the individual quality of life [27][28][29][30][31], as well as more general research works by Aaronson [32] and Rehse [33].…”
Section: Biofeedback For Quality Of Life Measurement and Modellingmentioning
confidence: 99%
“…Sin embargo, algunas investigaciones han constatado descensos más relevantes a partir de 4 semanas de entrenamiento 18 y de 6 semanas 16 . Tras 4 semanas de tratamiento respiratorio, realizado por el servicio de enfermería, pudieron observarse igualmente descensos en las medidas de ansiedad y estrés y mejoras en la calidad de vida, aunque solo en esta última con significación estadística (p = 0,04) 19 . Un entrenamiento respiratorio realizado en pacientes con síndrome de hiperventilación crónica mostró mejoría al cabo de 4 semanas, aunque los resultados fueron claramente significativos (p = 0,04) tras 8 semanas 20 .…”
Section: Introductionunclassified
“…Gerokomos. 2015;26(1):[18][19][20][21][22] José Ignacio Cea Ugarte, Asunción González-Pinto Arrillaga y Olga M.ª Cabo González…”
unclassified